2015
DOI: 10.1242/jcs.164160
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids regulate telomere clustering by affecting transcriptional levels of genes involved in telomere homeostasis

Abstract: In eukaryotic organisms, including mammals, nematodes and yeasts, the ends of chromosomes, telomeres are clustered at the nuclear periphery. Telomere clustering is assumed to be functionally important because proper organization of chromosomes is necessary for proper genome function and stability. However, the mechanisms and physiological roles of telomere clustering remain poorly understood. In this study, we demonstrate a role for sphingolipids in telomere clustering in the budding yeast Saccharomyces cerevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…The reaction was stopped by placing on ice, and adding 10 mM NaF and 10 mM NaN 3 . Lipids were subsequently extracted, of which one-half were hydrolyzed in mild alkali to deacylate glycophospholipids and identify base-resistant sphingolipids as described previously (Ikeda et al 2015). Radiolabeled lipids were analyzed by thin-layer chromatography in 9:7:2 v/v chloroform:methanol:4.2 N-ammonium hydroxide, and quantified using FLA-7000 (Fujifilm).…”
Section: Sphingolipid Labelingmentioning
confidence: 99%
“…The reaction was stopped by placing on ice, and adding 10 mM NaF and 10 mM NaN 3 . Lipids were subsequently extracted, of which one-half were hydrolyzed in mild alkali to deacylate glycophospholipids and identify base-resistant sphingolipids as described previously (Ikeda et al 2015). Radiolabeled lipids were analyzed by thin-layer chromatography in 9:7:2 v/v chloroform:methanol:4.2 N-ammonium hydroxide, and quantified using FLA-7000 (Fujifilm).…”
Section: Sphingolipid Labelingmentioning
confidence: 99%
“…In a previous study using strains of the BY4741 background, it was reported that the deletion of SUR2 causes a reduction in complex sphingolipid levels, while attenuating growth inhibition under an AUR1 -repressive condition 28 . Moreover, we observed reduced levels of complex sphingolipids when SUR2 was deleted in RH448 or RH6082 cells of a different background 32 33 . However, SUR2 deletion aggravated the growth inhibition caused by AbA ( Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Western blot analysis was performed as previously described (Ikeda et al , ). Blots were probed with rabbit polyclonal antibodies against Gas1 and CPY (gifts from Dr Riezman, University of Geneva, Switzerland) and then a peroxidase‐conjugated, affinity‐purified, anti‐rabbit‐IgG antibody (Sigma, St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%